Exploring the role of generative artificial intelligence in digital content marketing - Kauppinen, Risto Tapio (2024)
Several marketing activities have benefitted from the adoption of generative artifi-cial intelligence (GAI) tools and thus, shifted how digital content marketing (DCM) ac-tivities are approached by experts. The purpose of this study is to explore what kind of roles humans and GAI tools such as ChatGPT and Microsoft Copilot have in DCM. This study deployed qualitative research methods and conducted semi-structured inter-views with eight professionals from various levels of seniority working with DCM to determine how they view the role of GAI. The first key result of this study is that while individuals and firms have adopted GAI into their content creation processes, human editing and writing is still needed. This is leading firms to develop their own GAI tools that are trained with company data and can produce content with even less human oversight. The second key result of this study is that it highlights how companies have not been able to implement GAI tools into their customer relationship management (CRM) and marketing automation (MA) systems. Therefore, the role of GAI has been limited in marketing activities related to customer data. By implementing GAI into their current systems, firms will require less manual work towards extracting customer insights and optimizing customer journeys. The third key result is that firms have utilized GAI for enhancing their organic visibility on both social media and information search channels. The main applications for GAI stems from content production for these channels by using GAI programs to create visu-als and texts and contribute to supporting activities such as keyword research. This study contributes to the GAI in marketing literature and DCM literature streams by answering calls for research on the role of GAI and furthers the extant knowledge on how GAI is used for specific marketing activitiess related to DCM such as SEO. The main implication of this study to managers is to actively look for opportuni-ties to adopt a GAI tool for internal firm use and implement tools with GAI features specifically designed for certain tasks such as SEO.